Ginsenoside Compound K Assisted G-Quadruplex Folding and Regulated G-Quadruplex-Containing Transcription - Yan Zhang; Zhidong Qiu; Ming Zhu; Ye Teng (Molecules, 2021)
Ginsenoside compound K (CK) is one of the major metabolites of the bioactive ingredients in Panax ginseng, which presents excellent bioactivity and regulates the expression of important proteins. In this work, the effects of CK on G-quadruplexes (G4s) were quantitatively analyzed in the presence and absence of their complementary sequences. CK was demonstrated to facilitate the formation of G4s, and increase the quantity of G4s in the competition with duplex. Thermodynamic experiments suggested that the electrostatic interactions were important for G4 stabilization by CK. CK was further found to regulate the transcription of G4-containing templates, reduce full-length transcripts, and decrease the transcription efficiency. Our results provide new evidence for the pharmacological study of ginsenosides at the gene level.